A massive open online course on particle accelerators - Deleru, N; Faus-Golfe, A; Metral, E; Toes, J; Schmickler, H; Burt, G; Darve, C; Yogi, R; Møller, S; Burrows, P (JACoW Publishing, 2018)
The TIARA (Test Infrastructure and Accelerator Research Area) project funded by the European Union 7th framework programme made a survey of provision of education and training in accelerator science in Europe. This survey highlighted the need for more training opportunities targeting undergraduate-level students. This need is now being addressed by the European Union H2020 project ARIES (Accelerator Research and Innovation for European Science and Society) via the preparation of a Massive Open Online Course (MOOC) on particle accelerator science and engineering. We present here the current status of this project, the main elements of the syllabus, how it will be delivered, and the schedule for providing the course.